Modelling and simulation of chlorophyll fluorescence from photosystem II as affected by temperature. Issue 6 (1st December 2018) - Xia, Qian; Tan, Jinglu; Ji, Xunsheng; Jiang, Yongnian; Guo, Ya
Abstract : Emission of chlorophyll fluorescence (ChlF) from photosystem II (PSII) is affected by both plant status and environmental conditions. In this work, a state space model structure for ChlF from PSII with temperature as a variable model parameter was developed to provide insights into the temperature effects on photosynthesis and greenhouse temperature control. Experiments were carried out at 20, 25, and 30°C to validate the capability and flexibility of the developed model structure. Simulations of ChlF emission were performed for different temperatures. The results demonstrated the effectiveness of the ChlF model structure and the findings are useful for the development of greenhouse temperature control strategies.